DESIGN AND DEVELOPMENT OF THE MOSQPRAY APPLICATION USING EXTREME PROGRAMMING METHOD - Prayoga, Satrio Mukti; Defriani, Meriska; Sunandar, Muhamad Agus (RISTEC : Research in Information Systems and Technology, 2025)
This study aims to design and develop an Android application called MosqPray to help Muslims access prayer schedules automatically based on location and search for nearby mosques using the Google Maps API. The app includes prayer time reminders and favorite mosque saving features. The development method used is Extreme Programming (XP), which emphasizes short iterations and active user involvement. Observations of three similar apps revealed limited native mosque search features and issues with interface and ads. Testing shows MosqPray runs stably on Android 8.0 and above and provides accurate information. The app is expected to support timely prayer, especially in unfamiliar locations.